Revitalizing Low-Income Public Housing Through Community Participation in the UK - World Bank (Washington, DC, 2012)
Poverty is at the root of the problems facing many public housing projects in the U.K. today. Experience emerging from 100 low-income housing estates echoes findings from urban upgrading for the poor in developing countries. Tackling poverty and unemployment in low income communities cannot be left to the market alone. Community participation and full partnership with communities is key, but this is constrained by the push to achieve results quickly, as well as lack of agency interest and skills in working with poor communities as partners. Lasting change requires a strong national and regional policy framework, a new approach based on inter-agency cooperation, local delivery, and meaningful participation by local residents. Residents of such projects offer a significant resource for regeneration, particularly when they have established a foundation of local activity and organizational experience.